Chemical Profiling and Comparison of Sangju Ganmao Tablet and Its Component Herbs Using Two-Dimensional Liquid Chromatography to Explore Compatibility Mechanism of Herbs - Ji, Shuai; Liu, Zhan-Zhong; Wu, Jing; Du, Yan; Su, Zhen-Yu; Wang, Tian-Yun; Han, Jie; Yang, Dong-Zhi; Guo, Meng-Zhe; Tang, Dao-Quan (Frontiers in Pharmacology, 2018)
Sangju Ganmao tablet (SGT), a well-known Chinese patent medicine used to treat cold symptoms, is made from eight herbal medicines. In this study, an off-line hydrophilic interaction × reversed-phase two-dimensional liquid chromatography (HILIC × RP 2D-LC) method was developed to comprehensively separate the chemical constituents of SGT. Through optimization of the experimental conditions, a total of 465 peaks were finally detected in SGT, and the structures of 54 selected compounds were fully identified or tentatively characterized by quadrupole time-of-flight mass spectrometry (qTOF-MS) analysis. The established 2D-LC analysis showed high orthogonality (63.62%) and approximate 11-fold improvement in peak capacity (2399 and 1099, obtained by two calculation methods), in contrast to conventional one-dimensional RPLC separation. The eight component herbs of SGT were also respectively separated by using the 2D-LC system, and we found that a total of 12 peaks detected in SGT were not discovered in any component herbs. These newly generated chemical constituents would benefit better understanding of the compatibility mechanism of the component herbs. The strategy established in this study could be used for systematic chemical comparison of SGT and its component herbs, which contributes to exploration of herbal compatibility mechanism.